Shikhara (superstructure) of the southern Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The superstructure of the southern garbhagriha (sanctum sanctorum) is shekhari in style i.e., the central latina spires with rows of half spires added on either side. It comprises a mulamanjri (principal spire), uruh shringas (subsidiary spires leaning against the main spire), and shringas (miniature shrines). Divine figures adorn the shikhara's surface.